The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1116/1.4766183
|View full text |Cite
|
Sign up to set email alerts
|

Properties of stacked SrTiO3/Al2O3 metal–insulator–metal capacitors

Abstract: Articles you may be interested inVoltage linearity modulation and polarity dependent conduction in metal-insulator-metal capacitors with atomiclayer-deposited Al2O3/ZrO2/SiO2 nano-stacks Influence of precursor chemistry and growth temperature on the electrical properties of SrTiO 3 -based metalinsulator-metal capacitors grown by atomic layer deposition J. Vac. Sci. Technol. B 29, 01AC04 (2011); 10.1116/1.3525280 Impact of crystallization behavior of Sr x Ti y O z films on electrical properties of metal-insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The effects of the location of the leakage current blocking layer within the stack have been published elsewhere. 31 As evident from Figure 1, there are generally two different voltage regions with varying gradients within the leakage current density graph. Thus first a comparison of leakage current density of the investigated dielectrics was generated for the low-voltage region.…”
Section: Resultsmentioning
confidence: 96%
“…The effects of the location of the leakage current blocking layer within the stack have been published elsewhere. 31 As evident from Figure 1, there are generally two different voltage regions with varying gradients within the leakage current density graph. Thus first a comparison of leakage current density of the investigated dielectrics was generated for the low-voltage region.…”
Section: Resultsmentioning
confidence: 96%
“…For the conformal growth on three dimensional (3D) structured devices with high integration density, chemical vapor deposition techniques 29,30 and, in particular, ALD techniques, 15,31,32 were utilized. Although the requirements on the aspect ratio of 3D structures for ReRAM applications are still moderate, the future of high-density ReRAM will also be defined by more challenging 3D topologies.…”
Section: -28mentioning
confidence: 99%
“…However, the dielectric constant of this PECVD silicon nitride is relatively low and ranges only from 6 to 7, depending on the deposition chemistry and condition (10,12,14,19). Recently, studies have been performed to investigate the use of atomic layer deposition (ALD) method to deposit MIM capacitor dielectric material in semiconductor technologies (4,11,(20)(21)(22). Most of these studies were performed on Si technologies, and only a few have been performed on GaAs technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed on Si technologies, and only a few have been performed on GaAs technologies. This ALD method has been used to deposit films with high dielectric constant at low temperatures with excellent conformality and uniformity, and with good chemical, physical, and electrical characteristics (21)(22)(23)(24)(25). Furthermore, it has been reported that ALD nanolaminate of two or more materials can be tailored, adjusted, and controlled in order to obtain a film with all the characteristics that are desired and required (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%